La prévalence de l’hépatite virale B dans la wilaya de Mostaganem - BELGHAOUTI, Radia; BENDEHIBA, Samira (My University, 2017)
The hepatitis B (HBV) is one of different virus responsible for viral hepatitis . In the world , more than 2 billion peopole were infected by HBV and over 350 million of them have chronic infections. Markers serological are commonly used to confirm the diagnosis and / or help prognosis of infection acute or chronic HBV. The principal marker infection HBV is the presence of surface antigen (HBS Ag). Although holders can eliminate the HBS Ag and develop anti-HBS, it seems there is always a risk subsequent complications liver serious. The serological diagnosis is done by the method : ELISA (Enzyme Linked Immuno Sorbet Assay), it detects HBS Ag in the serum donors, siks internal and external during our probationary period in hospital Ain Tedeles – Mostaganem-. It was marked a low frequency the contamination by this virus for age groups 20 to 30 years and 50 to 60 years, however the prevalence of HBS Ag was significantly more important in elderly subjects 30- 40 years. Finally the information about remain the best ways to combat this infectious disease such that the awareness and information of the population to reduce the risk of transmission of this disease.
Keywords: HBV; HBS Ag; ELISA